Subependymal Zone: Immunohistochemically Distinct Compartment in the Adult Mammalian Forebrain - Jaroslav Mokrý; Dana Čížková; Jan Österreicher (Acta Medica, 2004)
The subependymal zone (SEZ) lining lateral walls of the lateral cerebral ventricles represents the site of active neurogenesis in the brain of adult mammals. Peroxidase immunohistochemistry performed in paraffin-embedded sections reveals that structural organization of the SEZ differs from other regions in the brain. The SEZ is devoid of synapses that are abundant in the adjacent striatal neuropil. Therefore immunostaining of synaptophysin detects sharp borders of the SEZ. Using immunophenotypization, we identified cell types constituting the SEZ in the intact rat forebrain. The presence of neural progenitor/stem cells was confirmed by finding of nestin-immunopositive cells. Detection of the astroglial marker GFAP confirmed that astrocytes represented major supporting elements responsible for creating a unique microenvironment of the SEZ. One type of the astroglia participated in covering surfaces of the blood vessels and boundaries of the SEZ. The second astroglial cell type formed branched elongated tubes that enwrapped other SEZ cell types with their cytoplasmic extensions. The interior of astrocytic channels was occupied with small densely aggregated NCAM-immunoreactive neuroblasts. Bipolar morphology indicated that these cells probably underwent migration. Immunodetection of other neuronal markers like β-III tubulin, MAP-2 and Pan neurofilaments identified positive cells in the neighbouring brain parenchyma but not in the SEZ. The rostral migratory stream (RMS) linked with the anterior SEZ had a similar structural arrangement. It contained a large amount of nestin+ and vimentin+ cells. The RMS consisted of GFAP+ astrocytic tubes ensheathing NCAM+ neuroblasts. On the contrary to the SEZ, the RMS neuroblasts expressed β-III tubulin. However, markers of postmitotic neurons MAP-2, Pan neurofilaments and synaptophysin were not expressed in the RMS. Our study describes a complex histological structure of the rat SEZ, identifies its individual cell types and demonstrates a usefulness of immunohistochemical detection of cell-specific markers in a study of microenvironment forming neurogenic zones in the mammalian brain.